Farnesyltransferase-inhibitors exert in vitro immunosuppressive capacity by inhibiting human B-cells - Xu, Shilei; Dolff, Sebastian; Mülling, Nils; Bachmann, Hagen S.; Dai, Yang; Lindemann, Monika; Sun, Ming; Witzke, Oliver; Kribben, Andreas; Wilde, Benjamin (Frontiers in Transplantation, 2023)
Objectives Farnesyltransferase inhibitors (FTI), which inhibit the prenylation of Ras GTPases, were developed as anti-cancer drugs. As additional target proteins for prenylation were identified in the past, it is likely that FTI have potential value for therapeutic purposes beyond cancer. The effect of FTI on B-cells remains unclear. To address this issue, we investigated the effects of in vitro FTI treatment on effector and regulatory B-cells in healthy controls and renal transplant patients. Methods For this purpose, B-cells were isolated from the peripheral blood of healthy controls and renal transplant patients. Purified B-cells were stimulated via Toll-like-receptor 9 (TLR-9) in the presence or absence of FTI. Regulatory functions, such as IL-10 and Granzyme B (GrB) secretion, were assessed by flow cytometry. In addition, effector B-cell functions, such as plasma cell formation and IgG secretion, were studied. Results The two FTI Lonafarnib and tipifarnib both suppressed TLR-9-induced B-cell proliferation. Maturation of IL-10 producing B-cells was suppressed by FTI at high concentrations as well as induction of GrB-secreting B-cells. Plasma blast formation and IgG secretion were potently suppressed by FTI. Moreover, purified B-cells from immunosuppressed renal transplant patients were also susceptible to FTI-induced suppression of effector functions, evidenced by diminished IgG secretion. Conclusion FTI suppress in vitro B-cell proliferation and plasma cell formation while partially preserving IL-10 as well as GrB production of B-cells. Thus, FTI may have immunosuppressive capacity encouraging further studies to investigate the potential immunomodulatory value of this agent.